Processing Fluency in Education: How Metacognitive Feelings Shape Learning, Belief Formation, and Affect. Issue 2 (3rd April 2017) - Reber, Rolf; Greifeneder, Rainer
Abstract : Processing fluency—the experienced ease with which a mental operation is performed—has attracted little attention in educational psychology, despite its relevance. The present article reviews and integrates empirical evidence on processing fluency that is relevant to school education. Fluency is important, for instance, in learning, self-assessment of knowledge, testing, grading, teacher–student communication, social interaction in the multicultural classroom, and emergence of interest. After a brief overview of basic fluency research we review effects of processing fluency in three broad areas: metacognition in learning, belief formation, and affect. Within each area, we provide evidence-based implications for education. Along the way, we offer fluency-based insights into phenomena that were long known but not yet sufficiently explained (e.g., the effect of handwriting on grading). Bringing fluency (back) to education may contribute to research and school practice alike.